Pemanfaatan Tomat sebagai Pupuk Organik Cair di Pasar Giwangan, Yogyakarta - Buana Perwita Sari; Bambang Suwerda; Siti Hani Istiqomah (Poltekkes Kemenkes Yogyakarta, 2017)
Yogyakarta’s Giwangan Market is a traditional market that non-stop open fo 24 hours, becauseit is the main market for fruits and vegetables. The waste generated from Giwangan Marketmostly in the form of organic waste, one of which is tomatoes waste. Tomato is a seasonal fruit,that have limited shelf life, i.e. only 3 days. Based on the preliminary survey, the average of tomato waste produced by all tomato seller in this market is 500 kilograms a day. The alternativesolution for this problem is changing the waste become liquid organic fertilizer. This researchwas a true experiment with post test only group design. There were two ingredient compositions used for yielding the fertilizer. Composition A was consisted of 10 kg tomat waste, 500ml molase, 100 ml used water of rice washing, 1000 ml old coconut water, and 7 liter clean water; and Composition B used same ingredients, except only 5 kg tomato waste. The data wereanalysed by using one way anova LSD tests at 0,05 significance level. The results of measurement of N, P dan K contents gained from Composition A and Composition B have not fulfilledthe requirement set by SNI 19-7030-2004; but for pH, the best results was from the Composition A. Suggestions for researchers who want to continue this study are: before making the liquid organic fertilizer, the waste tomatoes should be dried first; and any other vegetables orfruits containing potassium, nitrogen or phosphorus may be added in order to obtain better results